PELAKSANAAN OPERASI PASAR LUMBUNG PANGAN TERHADAP KESEJAHTERAAN MASYARAKAT - Wardani, Danastri Putri; Hardjati, Susi (Jurnal Pengabdian Masyarakat Sabangka, 2024)
This research is based on the East Java Food Barn Market Operation Program aimed at solving problems faced by the community due to soaring staple prices and to suppress inflation. The solution offered from this program is the implementation procedure so that it runs properly. The form of activity is in the form of observation of the implementation of the East Java food barn market operation in the community. Descriptive research method with a qualitative approach, focusing on the problem on the basis of facts carried out by means of observation or observation, interviews, and studying documents. The results in the study show that Market Operation is a program whose purpose is to maintain and ensure sufficient food availability and stable prices among the community. This program is implemented to fight high food price inflation and overcome food scarcity problems that can disrupt the welfare of the community. The market operation procedure is one of the efforts to improve the welfare of the community in East Java which is going well by implementing Market Operations in East Java for Community Welfare in order to meet their daily needs.